Composing affect: reflection on configurations of body, sound and technology in contemporary South African performance - Cilliers, Ilana (Rhodes University, Faculty of Humanities, Department of Drama, 2016)
This thesis engages with experiential performance modes through the lenses of phenomenology and affect theory. Because experiential performance relies per definition on personal, subjective 'experience', specific responses cannot be anticipated. However, by attempting to compose 'affect', a performance has the potential to 'move' an attendant towards response. Deleuze and Guattari define 'affect' as "an ability to affect and be affected"¦.a prepersonal intensity corresponding to the passage from one experiential state of the body to another and implying an augmentation or diminution in that body's capacity to act" (1987: xvi). One current strategy for manifesting affect in performance seems to be the ways in which different configurations of body, sound and technology are employed. The body is the means through which sound is received or 'experienced' in the phenomenological sense, but it can also act as a source for sonic material. The body is furthermore the means by which sonic technology is manipulated. It is the complex, reverberating relationships between body, sound and technology, and their potential for eliciting affective transformation, which is the focus of my enquiry. In the first chapter I unpack the roles of the natural phenomena, body and sound, and their complex relationships to affect. The chapter serves as philosophical basis for the rest of the investigation, and draws largely on works by philosophers Susan Kozel, Maurice Merleau-Ponty, Brian Massumi, Gille Deleuze and Félix Guatarri and sound theorists Don Ihde, Marshall McLuhan, Brandon LaBelle and Frances Dyson.In the remaining three chapters I discuss current South African theatre works that employ the strategy of placing emphasis on sound, sonic technology, and its relationship to the human body. These works are my own piece herTz (2014), Jaco Bouwer's pieces Samsa-masjien (2014) and Na-aap (2013), and First Physical Theatre Company's Everyday Falling (2010). While they range from being plays to physical theatre performances to performative experiments, they all place specific emphasis on sonic devices, drawing attention to sound by revealing microphones, speakers, midi boards, etc. to the attendants, and including the generation and manipulation of sound in the action of the performance.
Keywords: Uncatalogued